Perceived affordances and postures for lifting in child care. (3rd September 2017) - Doan, Jon; Awosoga, Olu; Provost, Trishell; Blinch, Jarrod; Hudson, Jessica
ABSTRACT: Childcare work appears to be full of the physical and mental risk factors frequently associated with chronic exertion leading to injury of the musculoskeletal system. The purpose of this study was to examine the affordances and mechanics for lifting a child, and to associate those mechanics with physical demands reports provided by experienced childcare workers. Participants perceived a smaller safe reaching distance to a child compared to a conventional handling target, despite the identical load and similar load distribution. This difference may reflect the influence of coupling (suitcase had 'good' coupling, child manikin had 'poor' coupling), or an increased concern for the safety of the child over the suitcase. While lifting at a smaller affordant distance could contribute to decreasing spinal loading from reactive moments, the greater trunk and knee flexions observed in child lifting may be contributing to childcare workers' musculoskeletal discomfort and injury in those regions.